Intellectual Capital and Its Impact on the Financial Performance of Russian Manufacturing Companies - Tatiana Andreeva; Tatiana Garanina (Foresight and STI Governance)
Intellectual Capital (IC) has been argued to be the key element of value creation in the contemporary economy. According to the results obtained in [Molnar, 2004] in the 1980s the share of tangible assets accounted for about 62% of market capitalization of companies on developed markets. However, by the start of the 2000s, their share fell to 16%. This has been widely supported by empirical research, but mainly based on the data from developed markets. The questions of how IC and its elements work on emerging markets remains under-researched due to a lack of empirical research devoted to this topic. The aim of the study is to provide empirical insight into the relationship between three main elements of IC (human, relational and organisational) and organisational performance of Russian companies, such as asset profitability, net sales growth and market share. The sample includes 240 Russian companies. Information about different elements of intellectual capital has been gathered with the help of a questionnaire that has been answered by the executive management of the companies included in the sample over the course of January-March 2015. The data is collected with the survey using the scales that have been already internationally. The findings based on regression analysis demonstrate that structural and human capital positively influence organisational performance, while relational capital does not.